2018
DOI: 10.3389/fmicb.2018.01547
|View full text |Cite
|
Sign up to set email alerts
|

MmpL3 as a Target for the Treatment of Drug-Resistant Nontuberculous Mycobacterial Infections

Abstract: Nontuberculous mycobacterial (NTM) pulmonary infections are emerging as a global health problem and pose a threat to susceptible individuals with structural or functional lung conditions such as cystic fibrosis, chronic obstructive pulmonary disease and bronchiectasis. Mycobacterium avium complex (MAC) and Mycobacterium abscessus complex (MABSC) species account for 70–95% of the pulmonary NTM infections worldwide. Treatment options for these pathogens are limited, involve lengthy multidrug regimens of 12–18 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 49 publications
0
51
0
Order By: Relevance
“…ICs 5 and 25 target the essential mycolic acid transporter, MmpL3, in MABSC. Previous studies have shown that ICs target the essential mycolic acid transporter MmpL3 (7,9,10,12,14). Here, we report that compounds 5 and 25 target the inner membrane transporter MmpL3 of M. abscessus, resulting in the abolition of the translocation of mycolic acids from the cytoplasm to the periplasmic space, ultimately causing cell death.…”
mentioning
confidence: 77%
“…ICs 5 and 25 target the essential mycolic acid transporter, MmpL3, in MABSC. Previous studies have shown that ICs target the essential mycolic acid transporter MmpL3 (7,9,10,12,14). Here, we report that compounds 5 and 25 target the inner membrane transporter MmpL3 of M. abscessus, resulting in the abolition of the translocation of mycolic acids from the cytoplasm to the periplasmic space, ultimately causing cell death.…”
mentioning
confidence: 77%
“…These TMMs are then converted into trehalose dimycolate (TDM) by the Ag85 complex in the cell envelope 18 . MmpL3 is essential as evidenced by a pre-existing rescue allele being required to generate an mmpL3 knockout 2, 14, 17, 19, 20, 21 , lack of mutants in high-throughput transposon mutagenesis screens 22, 23 , and studies that show rapid killing in vitro and in vivo in acute infection models when mmpL3 expression is conditionally inhibited 14, 19 . This makes MmpL3 an attractive target for drug development, with one of its inhibitors, SQ109, currently in clinical trials 24 .…”
Section: Introductionmentioning
confidence: 99%
“…These data strongly suggest that compounds from the structural class of benzothiazole cyclohexyl amides such as CRS400153 kill M. abscessus through the direct or indirect inhibition of MmpL3. The fact that CRS400153 showed no effect on the membrane potential and electrochemical pH gradient of Mtb intact cells and inverted membrane vesicles (data not shown) supports a direct mechanism of inhibition of the transporter (Li et al, 2018 ).…”
Section: Resultsmentioning
confidence: 64%